Interactive Visualization System for Psychological Topology - Yasunori Shiono; Chieko Kato; Koichiro Aoki; Kensei Tsuchida (IAES Indonesian Section, 2019)
Recently, there is increasing interest in mental support activities, including mental health care, counseling, and mental training in workplaces, schools, and sports teams. As a background to these things, various analysis methods have been developed to clarify and visualize the subject’s mental state based on these data. We tried to reveal and visualize the transition patterns of the subjects’ mental states by analyzing their utterances. Furthermore, we developed an interactive system of visualization of psychological state to support visual understanding of psychological topology. Features have been implemented to enable multidimensional data to visualize the movements shown on the SOM map. In this paper, we describe the system that can interactively visualize psychological states.